"Aux coins des rideaux fermés comme aux coins des bouches lasses”: finestre nella Recherche (Altre Modernità, 2015)
Different kinds of windows appear in the Recherche by Proust, defining not only the Narrator's perspective about space, but also his attitude toward artistic research. We will analyse three models of windows: firstly, a closed window, remote and mysterious, which marks the fictive boundaries of places from which the observer is left out; secondly, the open windows through which the Narrator watches Balbec's landscape in À l'ombre de jeunes filles en fleurs, while he composes sumptuous painting with words inspired by Impressionism. Those windows represent a screen between the Narrator and reality, a sort of veil which hides the empty shell of reality. Thirdly, we will study the series of windows closed from within, which symbolize the claustrophobic atmosphere of Albertine's captivity. A strange music, evocative and profound, will seep from those obscured windows to the Narrator's ears. Clearly, behind the subject of the window in the Recherche appears the theme of aesthetic creation and its connection with reality. We will explore this relation through the analysis of three “window scenes”, which suggest three phases of the Narrator's artistic research: painting, music, and finally literary description, which reveal in advance the architectonical structure of Proust's work.
Keywords: letteratura francese